2cscx+1=cscx+32\csc x+1=\csc x+32cscx+1=cscx+3
(−1)2−4(−1)+4\sqrt{\left(-1\right)^2-4\left(-1\right)+4}(−1)2−4(−1)+4
2x=3x+252x=\frac{3}{x}+\frac{2}{5}2x=x3+52
∫1−4x−9dx\int\frac{1}{\sqrt{-4x-9}}dx∫−4x−91dx
113 − 206113\:-\:206113−206
(8n−9)(8n+12)\left(8n-9\right)\left(8n+12\right)(8n−9)(8n+12)
Get a preview of step-by-step solutions.
Earn solution credits, which you can redeem for complete step-by-step solutions.
Save your favorite problems.
Become premium to access unlimited solutions, download solutions, discounts and more!